A legal research on regulating outer space activities in Malaysia / Muhammad Syafiqz Mohd Nasir - Mohd Nasir, Muhammad Syafiqz (2017)
This study is carried out to identify any law that governing and regulating any of outer space activities in Malaysia.it also will look min the adequacy of any existing law on space-related activities. Other than that, it is also to identify whether there is any country has Outer Space Act or any space related activities regulation that govern the activities itself literally. The references will look into all the outer space treaties and any legal instrument at international level that created the legal prospect which seem suitable for Malaysia legal system. This research showed the existing law in UK as the main reference to Malaysia due several aspect including the principle as the space player itself, the involvement by both countries at international level, the space institution and also the legal framework that being work by Malaysia which referring to UK as the main references. This is because each of the Acts has its own limitations and terms that have been covered. Furthermore, this also look into the legal comparison and capacity that establish by both nation. As non-human space flight favourite, Malaysia and UK had similarity in more developing the space related on downstream activity rather than upstream industry. Malaysia had launched our own national space policy in order to govern and take counter measure on this particular revolving new industry in Malaysia. We also took into account that our nation in the stages of final drafting the outer space act and to comply all the international space treaties in order to be a good space player in the future.